Generalized hooke law for relativistic membranes and p-branes - Zheltukhin, A.A. (Вопросы атомной науки и техники, 2012)
The character of elastic forces of relativistic membranes and p-branes encoded in their nonlinear equations is studied. The toroidal brane equations are reduced to the classical equations of anharmonic elastic media described by monomial potentials. Integrability of the equations is discussed and some of their exact solutions are constructed.